Comparative mitochondrial genomics of Shoveliteratura triangula (Orthoptera, Tettigoniidae, Meconematinae) and the first description of a female specimen - Mao, Shaoli; Yuan, Hao; Chang, Huihui; Shi, Fuming; Zhou, Yafu (Zootaxa, 2020)
This paper provides the first description of a female of Shoveliteratura triangula Shi, Bian & Change, 2011, as well as the complete mitogenome sequence using next-generation sequencing (NGS) technology. The length of the entire mitogenome was 16,152 bp and contained the typical gene arrangement, base composition, and codon usage found in other related species. The overall base composition exhibited a clear anti-G (10.8%) and AT bias (70.5%). The third codon positions in all protein-coding genes (PCGs) displayed high AT-content values (81.4%) in contrast to lower values of 64.2%/64.5% in the first/second positions. Two tandem repeats, 2.49 repeats of 112 bp and 3.65 repeats of 201 bp, contributed 1013 bp to the length of the S. triangula control region (CR). A T-stretch as a recognition sequence of the replication origin and more than one distinct tandem repeat in the CR were common in the Tettigoniidae mitogenomes. Both the maximum likelihood (ML) and Bayesian inference (BI) analyses supported each subfamily of the Tettigoniidae as a monophyletic group. The relationships of the subfamilies were as follows: (Lipotactinae (Hexacentrinae (Conocephalinae (Meconematinae (Bradyporinae, Tettigoniinae))))). The newly sequenced species S. triangula was most closely related to Pseudokuzicus pieli.